An Analytical Study of a Peaceful Organization, Takeko Engineering (Thailand) Co, Ltd. According to Buddhist Peaceful Means - Chantradilokrat, Kanokporn (วารสารสันติศึกษาปริทรรศน์ มจร, 2017)
This qualitative field thesis aims to: 1) study the conceptual idea of a peaceful organization according to Buddhist peaceful means, 2) analytically study the context of working and relationship among the members of Takeko Engineering (Thailand) Co, Ltd., and 3) analyze Takeko Engineering (Thailand) Co, Ltd. as a peaceful organization in accordance with Buddhist peaceful means. The tools of the research are studies from documentation and an in-depth interview with 9 key informants. From the analysis, it is found the following: 1. A peaceful organization is the organization everyone can work together happily with love, understanding, respect and trust by using the principles of Sangahavatthu which is giving knowledge, loving one another within the organization, including loving customers, speaking nicely with friendship, sharing to staff and their families, and the continuity of good behavior as the staff’s role model. 2. Takeko Engineering (Thailand) Co, Ltd. has got a family style of administrative policy with good after sales service to its customers; the staff devote themselves to the success of the organization while the internal relationship emphasizes the well-being and safety in working with worthily reciprocated pay for progress according to it staff’s abilities, plus a good a welfare for them. 3. It can be concluded as a “HEART” model of a peaceful organization according to Buddhist peaceful means of Takeko Engineering (Thailand) Co, Ltd. : “H” is hearty-feeling, “E” is empathy, “A” is Attention, “R” is Relationship and “T” is Trust, respectively.